A novel multi-target strategy for Alzheimer?s disease treatment via sublingual route: Donepezil/memantine/curcumin-loaded nanofibers - BÖCEKÇİ, VEYSEL GÖKHAN; GÜNDÜZ, OĞUZHAN; ERTAŞ, BÜŞRA (My University, 2022)
Drug delivery systems that not only show efficacy through multiple therapeutic pathways but also facilitate patient drug use and exhibit a high bioavailability profile represent a promising strategy in the treatment of Alzheimer???s disease (AD). Here, donepezil (DO)/memantine (MM)/curcumin (CUR)-loaded electrospun nanofibers (NFs) were produced for the treatment of AD. DSC, XRD, and FT-IR studies demonstrated the complete incorporation of the drug into PVA/PVP NFs. The disintegration profile was improved by loading the drugs in PVA/PVP with fast wetting (less than 1 s), the start of disintegration (21 s), and dispersion in 110 s. The desired properties for sublingual application were achieved with the dissolution of NFs in 240 s. The cell viability in DO/ MM/CUR-loaded NFs was similar to the control group after 48 h in the cell culture. DO/MM/CUR-loaded NFs enhanced the expressions of BDNF (13.5-fold), TUBB3 (8.9-fold), Neurog2 (5.6-fold), NeuroD1 (5.8-fold), Nestin (166-fold), and GFAP (115-fold). DO/MM/CUR-loaded NFs and powder of these drugs contained in these fibers were daily administered sublingually to intracerebroventricular-streptozotocin (icv-STZ) treated rats. DO/MM/ CUR-loaded NFs treatment improved the short-term memory damage and enhanced memory, learning ability, and spatial exploration talent. Results indicated that the levels of A??, Tau protein, APP, GSK-3??, AChE, and TNF-?? were significantly decreased, and BDNF was increased by DO/MM/CUR-loaded NFs treatment compared to the AD group. In the histopathological analysis of the hippocampus and cortex, neuritic plaques and neurofibrillary nodes were not observed in the rats treated with DO/MM/CUR-loaded NFs. Taken together, the sublingual route delivery of DO/MM/CUR-loaded NFs supports potential clinical applications for AD.
Keywords: Alzheimer ?s disease; Memantine; Donepezil; Curcumin; Electrospun nanofiber; MEMORY DEFICITS; IN-VITRO; SUSTAINED-RELEASE; DRUG-RELEASE; STEM-CELLS; STREPTOZOTOCIN; DONEPEZIL; DEMENTIA; BRAIN; ACID